Economics and Apologetics—The Ideology/Utopia of Laissez-Faire and its Discontents. Issue 3 (3rd July 2019) - Zafirovski, Milan
Abstract: This article explores elements of apologetics in conventional economics. It argues that much of the latter is apologetics in the form of the ideology or utopia of laissez-faire, and many of its representatives are apologists of the latter. The article first examines instances of unconditional laissez-faire apologetics and extreme apologists. Then it presents cases of qualified laissez-faire apologetics and moderate apologists. Lastly, it identifies some examples of laissez-faire non- and anti-apologetics and critics expressing discontent with apologetic economics. The article aims to contribute to a fuller understanding of the relationship between economics and social science overall and ideology, politics, and related non-scientific elements.